EVALUATION OF TECHNETIUM-LABELED RED CELLS USING Sn-kit - RUKSAWIN, Nisarut (The ASEAN Journal of Radiology, 2023)
The labeling yield of 99mTc-erythrocytes by our method is higher than 97% for blood drawn from 35 patients with polycythemia vera (Hct. 50%-74%). Quality control for tagging effciency was done both in vitro and in vivo by using ionization chamber and scintillation counter respectively. All experiments were conducted with sodium petechnetate which was not the first elution from a new generator. As a results of experiments reported here, a simplified and reproducible method has been developed for the preparation of 99mTc-labeled red blood cells, it consistently produces high yield in a closed sterile system with few mechanical-steps.